Agile THz-range spectral multiplication of frequency combs using a multi-wavelength laser - Shahab Abdollahi; Mathieu Ladouce; Pablo Marin-Palomo; Martin Virte (Nature Communications, 2024)
Abstract A breakthrough technology, on-chip frequency comb sources offer broadband combs while being compact, energy-efficient, and cost-effective solutions for various applications from lidar to telecommunications. Yet, these sources encounter a fundamental trade-off between controllability and bandwidth: broadband combs, generated in microresonators, lack free-spectral range or spectral envelope control, while combs generated with electro-optic modulators can be carefully tailored but are limited in bandwidth. Here, we overcome this trade-off through agile spectral multiplication of narrowband combs. Exploiting the nonlinear dynamics of a multi-wavelength laser under modulated optical injection, we achieve spectral multiplication at frequency offsets from 26 GHz to 1.3 THz. Moreover, on-chip control allows for nano-second switching of the frequency offset. Compatible with generic platforms, our approach can be scaled up to cover several THz. When combined with THz photomixers, our system could enable low-cost, compact, and power-efficient THz comb sources, paving the way towards a new generation of THz applications.